PWE-094 Setting Standards By Defining The Aims And Optimal Design Of The Inflammatory Bowel Disease (ibd) Multidisciplinary Team (mdt) Meeting. (9th June 2014) - Morar, P; Read, J; Arora, S; Hart, A; Sevdalis, N; Faiz, O; Edwards, C
Abstract : Introduction: The National IBD Audit revealed 75% of participating institutions undertake a weekly MDT meeting for IBD patients. There is however little evidence of its efficacy in this context and currently there is no guidance on how this intervention may be standardised and used effectively. 1–3 Providing a standardised framework for the IBD MDT meeting will enhance its capacity to establish effective quality improvement. The aim of this study is to use national expert consensus to define the aims, optimal design, format and function of an IBD MDT meeting. Methods: 25 semistructured interviews were undertaken with a multidisciplinary sample (5 surgeons, 5 gastroenterologists, 5 IBD nurse specialists, 5 pathologists and 5 radiologists), from 2 UK regions: the Southwest of England and London. Interviews were audiotaped and transcribed verbatim. A standardised interview protocol with a clearly defined coding framework was used. The interview protocol explored key themes encompassing the optimal design format of the IBD MDT: Purpose Processes Logistics Redesign Results: 28 interviews were performed across a multidisciplinary sample of healthcare professionals. Thematic analysis and coding demonstrated common markers for each theme. High ranking markers for each theme included: Purpose: Requires multi-disciplinary input; to share collective expertise; and to improve patient outcome. Processes: Good attendance; sharing workload with colleagues; proactive discussions; core members being clinicians, surgeons, radiologists, pathologists and nurse specialists all with IBD interests; facilities required including IT and an appropriate space to meet; provisions for internal feedback to the IBD MDT on MDT decision outcomes; submitting names in advance; an MDT coordinator. Logistics: Duration of 1 h; once a week; protected time; selective cases. Redesign: Single centre each running their own IBD MDT; 'hub and spoke' model. Conclusion: Defining key elements for an optimal design format for the IBD MDT is necessary to ensure quality of care and reduce variation in care standards. This study demonstrates the methodology used for construction of provisional standards for the IBD MDT through interviews from a multidisciplinary group. Selection and adjustments of these standards through expert consensus are required to validate measures. References: UK IBD Steering Group 2007 IBD Audit 2006: National Results for the Organisation and Process of IBD Care in the UK Group 2009 IBD Audit 2008: National Results for the Organisation and Process of IBD Care in the UK IBD Standards Working Group 2009 Quality Care: Service Standards for the Healthcare of People who have Inflammatory Bowel Disease (IBD) Disclosure of Interest: None Declared.